A novel antibody targeting TIM-3 resulting in receptor internalization for cancer immunotherapy. (9th November 2020) - Kuang, Zhihui; Li, Li; Zhang, Pan; Chen, Bingliang; Wu, Min; Ni, Haiqing; Yi, Shuai; Zou, Jia; Liu, Junjian
Abstract: Background: Strategies to reinvigorate exhausted T cells have achieved great efficacy in certain subpopulations of tumor patients. Blocking the antibodies that target programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 induces durable responses in Hodgkin's lymphoma, melanoma, renal and lung cancers. T cell immunoglobulin mucin-3 (TIM-3) is another well-defined inhibitory receptor that is expressed in terminally differentiated Th1/Tc1 cells, which produces interferon gamma and cytotoxic molecules. It is also significantly expressed on forkhead box P3+ regulatory T cells and innate immune cells such as dendritic cells and macrophages. Methods: By immunizing BALB/c mice with recombinant TIM-3 and screening of 20 000 hybridoma clones, we selected a monoclonal TIM-3-blocking antibody (IBI104), which shows great efficacy in vitro and in vivo . Results: IBI104 blocks phosphatidylserine interaction with TIM-3 but does not interfere with the interaction of TIM-3 with galectin-9 in ELISA assays. However, in vitro administration of IBI104 induces the potent internalization of TIM-3 in activated T cells to the extent that it will shut down the entire TIM-3 mediated signaling regardless of the ligands. IBI104 shows potent anti-tumor efficacy when combined with anti-PD1 in vivo . Conclusions: Our results suggest that IBI104 is a promising blocking antibody for TIM-3-mediated suppressive signaling and can serve as effective cancer immunotherapy, especially in combination with anti-PD1.